Being a victim or an aggressor: Different functions of triadic post‐conflict interactions in wolves (Canis lupus lupus). Issue 6 (20th April 2015) - Cordoni, Giada; Palagi, Elisabetta
<x xml:space="preserve">Abstract</x> Animals adopt different behavioral strategies to cope with the conflict of interests coming from the competition over limited resources. Starting from the study on chimpanzees, post‐conflict third‐party affiliation (the affiliative contact provided by a third‐party toward the victim—VTA—or the aggressor—ATA) was investigated mainly in primates. Later, this post‐conflict mechanism has been demonstrated also in other mammals, such as wallabies, horses, dolphins, domestic dogs, and wolves. Here, we present data on triadic post‐conflict affiliation in wolves (Canis lupus lupus) by exploring some of the hypotheses already proposed for primates and never tested before in other social mammals. In this carnivore species, the study of VTA and ATA revealed that these strategies cannot be considered as a unique behavioral category since they differ in many functional aspects. VTA serves to protect the victim by reducing the likelihood of reiterated attacks from the previous aggressor and to reinforce the relationship shared by the third‐party and the victim. On the other hand, ATA has a role in bystander protection by limiting the renewed attacks of the previous aggressor toward uninvolved group‐members (potential third‐parties). In conclusion, exploring VTA and ATA gives the opportunity to concurrently demonstrate some functional differences in triadic post‐conflict affiliation according to the different targets of bystanders (victims or aggressors). The data comparison between primates and other social mammals should permit to open new lines of research. Aggr. Behav. 41:526–536, 2015. © 2015 Wiley Periodicals, Inc.